Maternal employment effects of paid parental leave - Annette Bergemann; Regina T. Riphahn (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
We study the short, medium, and long run employment effects of a substantial change in the parental leave benefit program in Germany. In 2007, a means-tested parental leave transfer program, which had paid benefits for up to two years, was replaced by an earnings related transfer, which paid benefits for up to one year. The reform generated winners and losers with heterogeneous response incentives. We find that the reform sped up the labor market return of all mothers after benefit expiration. Likely pathways for this substantial reform effect are changes in social norms and mothers' preferences for economic independence.
Keywords: J13; J21; 330; female labor supply; maternal labor supply; parental leave; parental leave benefit; child-rearing benefit